In Vitro Antioxidant Properties of Dichloromethanolic Leaf Extract of (Fresen) as a Promising Antiobesity Drug - Wycliffe Arika PhD; Cromwell Mwiti Kibiti PhD; Joan Murugi Njagi PhD; Mathew Piero Ngugi PhD (SAGE Publishing, 2019)
The acquisition of ethnobotanical information from traditional practitioners remains an empirical aspect of understanding the ethnopharmacology research. However, integration of information on chemical composition of plant extracts and their pharmacological activities forms a key resource for synthesis of new and effective therapeutics. In traditional African medicine, Gnidia glauca has folkloric remedies against obesity and its associated oxidative stress-mediated complications. However, the upsurge in its use has not been accompanied with scientific validations to support these claims. The present study aimed to determine the antioxidant potential of G glauca as a promising antiobesity agent. The antioxidant effects of the extract were assessed against 1,1-diphenyl-2-picrylhydrazyl, hydroxyl, hydrogen peroxide, nitric oxide, and superoxide radicals as well as lipid peroxidation, iron-chelating effect, and ferric-reducing power. Phytochemical analysis was conducted using gas chromatography linked to mass spectrophotometry. The results revealed that G glauca exhibited scavenging activities against all radicals formed. Besides, the extract showed iron chelation and ferric reducing abilities. The extract indicated a lower half maximal inhibitory concentration value than the standards used. For instance, the extract inhibited 50% of the formation of 2,2-diphenyl-1-picrylhydrazine at the concentration of 1.33 ± 0.03 mg/mL relative to 1.39 ± 0.06 mg/mL of the standard, vitamin C at 1% confidence limit. Similarly, the extract scavenged 50% of hydroxyl radical at 204.34 ± 10.64 μg/mL relative to 210.05 ± 8.80 μg/mL of gallic acid. The extract also contained various phytochemicals that have been associated with antiobesity effects. The synergistic effects of these phytocompounds increase their bioavailability and action on multiple molecular targets thereby correcting obesity-induced oxidative stress.